Artificial Intelligence and Sustainability in Architecture: Scientific mapping in WoS with Biblioshiny (International Journal of Built Environment and Sustainability, 2024)
This paper explores the evolution of academic debate and research in the field of architecture on AI and sustainability up to 2023. It focuses on the quantitative development of scientific publications on AI, the key countries and organizations behind these publications, key research topics and areas, and whether and how these publications address sustainability. A total of 428 international scientific publications (peer-reviewed articles, reviews and proceedings) on AI and sustainability in architecture were identified in the Web of Science database between 2020-2023. It has been noticed that the number of publications on artificial intelligence is increasing rapidly. Since 2021, a significant increase in the number of publications is observed. The countries with the highest number of publications are China (59%), USA (17%) and UK (15%), while the most frequently used keywords in publications are "performance" (13%), "design" (9%) and "model" (8%). The journals with the highest number of publications are Building and Environment (26%), Buildings (16%) and Journal of Building Engineering (14%). In the most cited papers, it was seen that AI is used to achieve goals such as implementing sustainability principles, reducing environmental impacts and increasing energy efficiency. As a result, the concept of sustainability is integrated into research on artificial intelligence as one of the most important concepts of future cities and architecture.
Keywords: Artificial intelligence, Web of Science, Biblioshiny, Sustainability, Architecture, Bibliometric analysis